Le controfigure di Dio. Da Blade Runner ad Avatar (Altre Modernità, 2011)
The issue of the relationship between the creator and his/her creature has been often dealt with  in dystopia and science fiction films, and in recent times it has taken on a specific flavor, less related to the implications of science and more connected to a symbolic dimension that goes  back to the Bible as a fruitful reservoir of myths and archetypes. The Biblical parable of the creation  in particular flows into narratives recalling familiar names and places, but deeply revising the  creator/creature relationship, that is unfolded through the poetic unacceptability of death in Blade  Runner (1982) and the possibility of a new life in a new body dwelling in the fictional Eden of Avatar (2010).